ANALISIS FOOD AND BEVERAGE CONTROLLER TERHADAP LABA FOOD AND BEVERAGE DEPARTMENT (Studi Kasus Restoran Hotel Di Jakarta) - Swantari, Anita; Wicaksono, Haryo; Festivalia, Filma (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2017)
Cost Control in a hotel is a part of the function of carrying out the task of cost control, recording the inventory of raw materials for food and beverages, where the Food Controller perform the recording of special costs associated with the cost of food (Food Cost), while the Beverage Controller is part of carrying out the recording Special costs associated with the cost of drinks (Beverage Cost). Research Objective, food and beverage inventory turn over, percentage of Food Cost and Beverage Cost, Average Check of Food and Beverage Service, Labor Cost, Profit Department of Food and Beverage. The data retrieval procedure uses the primary data, such as: conducting interviews to the Food and Beverage Controller. Secondary data are: Profit Loss F & B Department Period December 2015. The result of the research showed that: Food Cost Percentage reached 33.9% from budgeted 35%, meaning 1.1% below budget, Beverage Cost reached 22.44% from budgeted 25 %, Meaning 2.56% below budgeted, Labor Cost Percentage can be achieved 19.75% of budgeted at 24.0%, means 4.25% below budget, Percentage of Department Profit achieved 33.7 % Of the budgeted amounted to 28.6% in other words 5.1% above the budget.